Pengaruh Penggunaan Metode Pembelajaran Gasing (Gampang, Asyik dan Menyenangkan) Terhadap Hasil Belajar Matematika Siswa Kelas III SDI Sikumana 2 Kota Kupang - Amtiran, Chantika Angelin; Nahak , Kristina E. Noya; Nitte , Yulsy Marselina (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The top learning method is a learning process that makes it easier and more fun for students to learn. It is expected that the spinning top learning method can enhance student learning outcomes in mathematics lessons. The aim of this research is to determine the effect of using the spinning top learning method (easy, fun and enjoyable) on students' math learning outcomes on multiplication arithmetic operations for class III SDI Sikumana 2. This type of research is quantitative research and is categorized as Quasi-Experimental, using a non-equivalent control group experimental design. The study's findings indicate that, when comparing the posttest scores for the experimental and control groups using the t-test, the average difference is 23.53, or 84.82 > 61.29. Additionally, the results of the Independent Samples Tests, or hypothesis testing, indicate that the sig. (2-tailed) t-test for the equality of means is 0.000 < 0.05, which means that Ha is accepted and H0 is rejected. The conclusion of this research is that the top learning method (easy, fun, and enjoyable) has a significant impact on the learning outcomes of third-grade students at SDI Sikumana 2 in Kupang City.